Urgensi Strategi Pembelajaran Karakter Pada Anak Usia Dini - Samsul Bahri (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2019)
This study dicusses the issue of the urgency of character learning strategies in early childhood. This study uses descriptive analysis methods and authoritative resources related to the world of learning. This study proves that character building in early age students is very crucial. Therefore, character learning strategies must be begun Moral knowing / learning to know, Moral Loving / Moral Feeling, Moral Doing / Learning to do. These three strategies in learning can be carried out if the teachers First, apply a modeling approach or uswatun hasanah that is to socialize and uphold moral values ​​that are true through models and examples. Second, explain or clarify to students continuously about various good and bad values. Third, implementing character-based education. This can be done by applying a character-based approach to each subject. Keywords: learning strategy, character, modelReferencesAkbar, Sa’dun. (2011). Revitalisasi Pendidikan Karakter di Sekolah Dasar. Naskah Pidato Pengukuhan Guru Besar Universitas Negeri Malang. Azra, Azyumardi. (2002). Paradigma Baru Pendidikan Nasional. Jakarta: Kompas.Dewantara, HM. Hajar. (2012). Pendidikan Karakter; Pemberdayaan Guru Agama dalam Pembentukan Karakter Islami, Yogyakarta, Pusat Penelitian dan Pengembangan Pendidikan Islam, FIAI UII, p. 8-10.Dimyati dan Mudjiono. (2006). Belajar dan Pembelajaran. Jakarta: Rineka Cipta. Fatihah, N., & Difla Nadjih. (2017). Hubungan Pendidik Dan Terdidik Dalam Al-Quran. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 7(2), 1689–1699. https://doi.org/10.1017/CBO9781107415324.004Hasbullah, Hasbullah. (2018). Karakteristik Pendidikan Islam Menurut Imam Al-Ghazali (Proses Pendidikan Islam Yang Berkelanjutan Dan Berangsur-Angsur). aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, v. 3, n. 2, p. 81-88, Haroen, H. (2018). Gaya Belajar Siswa Bagi Burhanuddin Zarnuji. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 8(1), 17–34.Kusumawati, Intan. (2016). Pengembangan Karakter Siswa Raudlatul Athfal Berbasis Pendidikan Agama Islam. Aṣ-Ṣibyan Jurnal Pendidikan Anak Usia Dini, 1(2), 131–139.Langgulung, Hasan. (1994). Manusia Dan Pendidika. Jakarta: Pustaka Al-Husna. Langgulung, Hasan. (1985). Pendidikan dan Peradaban Islam; Suatu Analisa Sosio-Psikologi. Jakarta: Pustaka Al-Husna. Langgulung, Hasan. (2001). Pendidikan Islam Abad 21. Jakarta. Al-Husna Zikra. Langgulung, Hasan. (2002). Peralihan Paradigma Dalam Pendidikan Islam dan Sains Sosial. Jakarta: Gaya Media Pratama. Langgulung. Hasan. (1992). Teori-Teori Kesehatan Mental; Perbandingan Psikologi Modern dan Pendekatan Pakar Pendidikan Islam. Kijang Selangor: Pustaka Huda. Madjid, Abdul dan Andayani. (2011). Pendidikan Karakter dalam Perspektif Islam. Bandung: Remaja Rosdakarya. Megawangi, Ratna. http/www. langit Perempuan. Com. pelopor Pendidikan Holistik berbasis karakter, diakses 23 april 2013Murshafi, Muhammad Ali. (2009). Mendidik Anak Agar Cerdas dan Berbakti. Surakarta: Ziyad Visi Media. Nata, Abuddin. (2012). Kapita Selekta Pendidikan Islam. Jakarta: Grasindo. Nata, Abuddin. (2005). Pendidikan Menurut Perspektif Al-Qur’an. Jakarta: UIN Jakarta Press. Nata, Abuddin. (2009). Perspektif Islam tentang Strategi Pembelajaran. Jakarta. Kencana. Nizar, Samsul. (2012). Pengantar Dasar-Dasar Pemikiran Pendidikan Islam. Sahlan, Asmawan dan Angga Teguh Prastyo. (2012). Desain Pembelajaran Berbasis Pendidikan Karakter. Jogjakarta: Ar-Ruzz. Media. Setiani & Difla Nadjih. (2016). “Pembentukan Karakter Anak Usia Dini Melalui Pendidikan Agama Islam Di TK ABA Kalibulus Rogobangsan Bimomartani Ngemplak Sleman,” Ulumuddin : Jurnal Ilmu-Ilmu Keislaman Volume 6, Nomor 2, h. 125-136Soebijantoro. (2006). Kecerdasan Emosional dalam Konteks Hidden Curriculum. Jurnal Pendidikan. Vol. 12 No. 1. Suwito. (1995). Konsep Pendidikan Ahklak Menurut Ibn Miskawaih. Disertasi. Pascasarjana IAIN. Jakarta. Zubaidi. (2012). Desain Pendidikan Karakter, Konsepsi dan Aplikasi dalam Lembaga Pendidika. Jakarta: Kencana.